Association of the triglyceride‒glucose index with subclinical right ventricular systolic dysfunction in type 2 diabetes mellitus patients - Yan-fei Bian; Li Fan; Ling Cui; Xiang-ting Song (Scientific Reports)
Abstract The triglyceride‒glucose (TyG) index is associated with the development and prognosis of cardiovascular disease. The relationship between it and subclinical right ventricular (RV) systolic dysfunction in type 2 diabetes mellitus (T2DM) patients remains unclear. This study aimed to investigate this relationship in T2DM patients. A total of 170 T2DM patients were enrolled. The TyG index was calculated and then stratified into tertiles: the T1 group (TyG index ≤ 9.1495, n = 52), the T2 group (9.1495 < TyG index ≤ 9.7611, n = 54), and the T3 group (TyG index > 9.7611, n = 52). RV systolic function was evaluated in terms of RV free-wall longitudinal strain (RV FWLS). One-way analysis of variance revealed significant differences in the RV FWLS among the three groups. As the TyG index increased, the severity of RV systolic dysfunction increased. After adjusting for age and sex, the multivariate logistic regression analysis revealed that a higher TyG index was significantly associated with a RV FWLS < 20%, which was maintained after adjusting for body mass index (BMI), systolic pressure (SBP), left ventricular global longitudinal systolic strain (LV GLS), hypertension, and dyslipidemia. In T2DM patients, a higher TyG index was significantly associated with subclinical RV systolic dysfunction independent of other cardiovascular risk factors.